Implementasi “The Flash” New Character Building Dalam Upaya Meningkatkan Revolusi Mental Karyawan PT. Swabina Gatra - Amelia, Nabila; Prianggi Amelasasih (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
In the current global era, character building is needed in all fields, especially in companies that want their human resources to be better at work. "The Flash" New Character Building is a form of training for PT Swabina Gatra in creating employees who are competent and have active, flexible, intelligent and humble personalities. The method used in this research is descriptive qualitative, by interviewing trainees and training participants directly and making observations during the activity. The new findings that occurred when this training was carried out were changes in the participants' mentality to become more agile and adaptive to the surrounding environment, the presence of stimulus and The response from the trainer makes the participants have higher motivation and enthusiasm. Regular training programs are carried out with the aim of being a refreshing activity for employees. The implications of The Flash New Character Building training have positive implications in improving personal quality, performance and interpersonal relationships of individuals, as well as forming a good organizational culture